Chromium‐induced diffuse dermatitis with lymph node involvement resulting from Langerhans cell histiocytosis after metal‐on‐metal hip resurfacing. (1st June 2015) - Bizzotto, N.; Sandri, A.; Trivellin, G.; Magnan, B.; Micheloni, G.M.; Zamò, A.; Bernardi, P.; Sbarbati, A.; Regis, D.
Summary: Total hip arthroplasty (THA) is a highly effective surgical treatment for severe joint involvement. However, due to the release of metal ions in the blood, the patients who undergo hip replacement with metal‐on‐metal (MOM) bearings may develop signs of allergic skin disease. We report a case of a 60‐year‐old man who had received MOM hip resurfacing 5 years earlier for osteoarthritis. He presented with a 3‐year history of diffuse dermatitis that did not respond to antihistamines and corticosteroids and also had elevated serum levels of chromium and cobalt. A patch test revealed chromium‐sulfate hypersensitivity. A skin biopsy showed nonspecific perivascular lymphocytic infiltrate associated with histiocytes. A biopsy of an inguinal lymph node demonstrated large aggregates of Langerhans cells, suggesting type IV delayed‐type hypersensitivity. The prosthesis was replaced using ceramic‐on‐ceramic bearings and the dermatitis resolved after 3 months. The lymph nodes decreased in volume and the serum chromium levels normalized within 24 months of revision surgery. The high levels of serum ions associated with the metal debris from MOM‐THAs may induce sensitization and type IV hypersensitivity reactions. Replacing the prosthesis using alternative coupling surfaces is the only approach that has the capacity to resolve these symptoms. Physicians who are not familiar with this issue may misdiagnose systemic symptoms and provide inadequate treatment.